Effect of static magnetic field on marine mollusc Elysia leucolegnote - Fei, Fan; Zhang, Peng; Li, Xinyu; Wang, Shun; Feng, Erhui; Wan, Yinglang; Xie, Can (Frontiers in Molecular Biosciences, 2023)
Artificial magnetic fields are unavoidable environment for offshore marine organisms. With the substantially increasing submarine cables, the impact of magnetic field generated by cables on marine organisms has gradually attracted people's attention. However, there are few studies on the effect of magnetic field on molluscs. To explore whether magnetic fields could interfere with the physiological functions of offshore molluscs, here we systematically analyzed the change of metabolism and transcriptome of Elysia leucolegnote exposed to either geomagnetic field or 1.1 T static magnetic field. The blood glucose and lipid levels, as well as the activities of antioxidant enzymes in E. leucolegnote were significantly increased upon the exposure to high static magnetic field for 10 days. Meanwhile, the activities of enzymes related to digestive performance and liver functions were decreased. Possible mechanisms were further revealed through comparative transcriptome analysis. A total of 836 differentially expressed genes were identified, 352 of which were up-regulated and 484 of which were down-regulated after exposure to the high static magnetic field. The up-regulated differential genes were mainly concentrated in lysosomal and apoptotic pathways, and down-regulated differential genes were mainly involved in digestive and immune systems including phagocytosis. This pattern was further confirmed by RT-qPCR analysis. In conclusion, prolonged exposure to a 1.1 T static magnetic field increased oxidative stress and blood glucose and lipid levels, and decreased immunity and physiological conditions in E. leucolegnote. The data we presented here provides a comprehensive view of metabolism change and gene expression pattern of E. leucolegnote exposed to static magnetic field. It may expand our knowledge on the magnetic field effects on offshore mollusc at molecular level, and contribute to clarification of the interaction between marine animals and artificial magnetic fields, which is certainly ecologically important.